Recent Study on IoT Based Embedded Smart Lock Control System - Jasim, Hasan Bakheet (New Insights into Physical Science Vol. 13, 2021)
Smart home security and remote monitoring have become vital and indispensable in recent times, and with the advent of new concepts like Internet of Things and development of advanced authentication and security technologies, the need for smarter security systems has only been growing. . In recent times the need for security and surveillance has become vital in many areas such as homes, offices, banks, etc. The design and development of an intelligent web-based door lock control system using face recognition technology, for authentication, remote monitoring of visitors and remote control of smart door lock has been reported in this paper. This system uses Haar-like features for face detection and Local Binary Pattern Histogram (LBPH) for face recognition. The system also includes a web-based remote monitoring, an authentication module, and a bare-bones embedded IoT server, which transmits the live pictures of the visitors via email along with an SMS notification, and the owner can then remotely control the lock by responding to the email with predefined security codes to unlock the door. This system finds wide applications in smart homes where the physical presence of the owner at all times is not possible, and where a remote authentication and control is desired. The system has been implemented and tested using the Raspberry Pi 2 board, Python along with OpenCV are used to program the various face recognition and control modules. This paper also explores the immense potential of computer vision in general and face recognition, in particular, the possibilities of IoT in home security and automation. The versatility and prowess of Linux operating system, the Python programming language, and the OpenCV library have also been explored, in depth.